A Study of Affixation In West Simeulue Language - Amin, Fadrisal; Raflis, Raflis (Jurnal Ilmiah Pendidikan Scholastic, 2023)
This study discusses the type of affixation, especially prefixes and suffixes in the West Simeulue language. This study aims to find what types of prefixes and suffixes are in West Simeulue language. The method used in this research is descriptive qualitative. The data in this thesis are in the form of words, which are taken through an interview process with informants in the form of students who come from Simeulue Island and are native speakers of West Simeulue Language who are in the Padang City West Sumatera. Data collection techniques based on known data regarding the types of Prefix and Suffix affixes in the West Simeulue Language. The results of this study are that there are several types of prefixes and suffixes in West Simeulue language, in the prefix there is pattern form, prefix Ma-+ noun = verb, prefix Ma- + adjective = verb, prefix –Ma + verb = verb, prefix –Ni + noun = Adjective, Prefix –Mam + verb = Verb, prefix –Mang + noun = Verb, prefix Mang- + verb= Verb and in the suffix there is a pattern form that is slightly different from prefix, in the suffix verb + suffix -An= noun, verb + suffix -Ni = adjective, adjective + suffix –Ni = adjective, noun + suffix –I = verb and verb + suffix –I = verb